2020
DOI: 10.1111/jerd.12639
|View full text |Cite
|
Sign up to set email alerts
|

Allogeneic cortical struts and bone granules for challenging alveolar reconstructions: An innovative approach toward an established technique

Abstract: Objective: The shell technique is a well-established procedure for GBR with which extensive osseous defects can be predictably restored by using cortical bone struts harvested from various intraoral aspects. Recent publications have demonstrated comparable results for autologous and allogeneic bone grafts, whereas the evidence on allogeneic cortical struts remains limited. Clinical considerations: In this case series, we demonstrate the regeneration of five complex alveolar bone defects in four patients with s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 31 publications
1
12
0
Order By: Relevance
“…Re-investigation at implant placement demonstrated a sufficient bone remodeling and vascularization within the three-dimensional CP containers [53]. This can be confirmed by our histological findings.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Re-investigation at implant placement demonstrated a sufficient bone remodeling and vascularization within the three-dimensional CP containers [53]. This can be confirmed by our histological findings.…”
Section: Discussionsupporting
confidence: 86%
“…A case series reported about 4 patients with alveolar ridge augmentation using CP, allogeneic granules and a porcine pericardium membrane. Re-investigation at implant placement demonstrated a sufficient bone remodeling and vascularization within the three-dimensional CP containers [ 53 ]. This can be confirmed by our histological findings.…”
Section: Discussionmentioning
confidence: 99%
“…In initially disclosed case reports, the integration of human allogeneic bone plates and autogenous bone chips seems to be a viable substitute to autogenous implants in complex bone augmentation procedures; that being said, these researches were often case-controlled cohorts with no proper comparative studies published in credible animal models for in-depth preclinical evaluation. [41,50,52] Several studies have reported the reduction bone resorption rate and modulation of bone turnover and formation by using barrier membranes over augmented bone blocks. [53] [45, 54] These adjunctive interventions prompt us more towards developing a reliable animal model to provide a solid biological basis for furher in-vivo testing of bone grafting techniques to optimize the clinical outcome.…”
Section: Discussionmentioning
confidence: 99%
“…[49] With the current usage of human allogeneic bone cortices, further intraoral or extraoral bone block harvesting can indeed be skipped, minimising the total risk of problems and patient morbidity while providing clinical outcomes equivalent to autogenous bone shells. [41,50,51] Several clinical report indicated favorable outcomes with human allogeneic bone blocks for bone grafting procedures conducted according to the osseous shell technique. [41,50] While there is little evidence on the use of xenogenic and allogeneic particulate bone material and blocks in various forms, there is much less on the use of allogeneic cortical plates for the shell approach.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation